(untitled) (Annals of Medical Research, 2022)
Aim: The aim of this study is to investigate the co-occurrence of thyroid masses (TM) and breast masses (BM) and to examine related demographic features. Materials and Methods: The study included female patients; who were followed up in the general surgery outpatient clinic in the years between 2015 and 2020 because of thyroid nodules and underwent breast ultrasonography concurrently. Participants were divided into two groups as group-1 with the co-occurrence of thyroid and breast masses and group-2 with a TM but having no BM. The two groups were compared for age, body mass index (BMI), the number of children, the length of breastfeeding, TM size, TSH levels, vitamin D levels, and smoking status. Results: The study included 267 patients with thyroid nodules. Of the patients; 70.03% had comorbid BM but 29.96% had no BM. No statistically significant differences were found in age, smoking status, BMI, TSH levels, vitamin D levels, and thyroid nodule size between the two groups (p> 0.05). The number of births was fewer and the duration of breastfeeding was shorter in the group of patients having BM concomitantly (p <0.001). There was not a correlation between the size of TM and the size of BM (p: 0.839, r: 0.012). Conclusion: In our study, it was found that most of the patients with thyroid nodules also had a mass in their breasts and this finding was associated with the duration of breastfeeding, the number of births, and the vitamin D level.